2016
DOI: 10.3413/nukmed-0753-15-07
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission mammography in the diagnosis of breast cancer

Abstract: PEM is capable of differentiating breast tumours from benign lesions with 100% sensitivity along with a high specificity of 96%, when a threshold of PUVmax >1.9 is applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Claustrophobia is one of the most common phobias experienced by both men and women around the world, which leads some patients preferring not to choose such devices [19]. Specificity (%) 98.5 [23] 96.9 [23] 80.7 [30] 88.5 [35] 89.7 [40] 85 [45] 89 [49] 71.4 [53] 87 [58] 96 [62] 59.5 [67] 71 [72] 89.4 [78] Sensitivity (%) 66.1 [23] 69.1 [23] 92 [30] 72.6 [35] 82 [41] 90 [45] 95 [49] 100 [53] 91 [58] 95 [63] 96.4 [67] 87 [72] 95.6 [78] Total Scan Time 5 sec. [24] 6 sec.…”
Section: Jinst 15 C05029mentioning
confidence: 99%
“…Claustrophobia is one of the most common phobias experienced by both men and women around the world, which leads some patients preferring not to choose such devices [19]. Specificity (%) 98.5 [23] 96.9 [23] 80.7 [30] 88.5 [35] 89.7 [40] 85 [45] 89 [49] 71.4 [53] 87 [58] 96 [62] 59.5 [67] 71 [72] 89.4 [78] Sensitivity (%) 66.1 [23] 69.1 [23] 92 [30] 72.6 [35] 82 [41] 90 [45] 95 [49] 100 [53] 91 [58] 95 [63] 96.4 [67] 87 [72] 95.6 [78] Total Scan Time 5 sec. [24] 6 sec.…”
Section: Jinst 15 C05029mentioning
confidence: 99%
“…The maximum PUV for a region of interest (PUVmax) has been shown to be superior to other quantitative measures such as lesion to background (LTB) ratio for differentiating between benign and malignant tissue due to the simplicity and reproducibility of PUVmax 27 . Muller 28 suggested a threshold value of PUVmax >1.9 as predictive of malignancy based on an analysis of 108 patients. Other studies 1,27 have found it difficult to use a discriminatory threshold for predicting malignancy, although median PUVmax for malignancies was significantly greater than that for benign lesions.…”
Section: Quantificationmentioning
confidence: 99%
“…No specified threshold for malignancy exists, although a recent study comparing LTB and PUV max recommended the use of PUV max due to its simplicity and reproducibility 26 . Another study 27 evaluated PUV max and LTB using healthy tissue in the contralateral breast as background and found that both PUV max and LTB were significantly higher for tumors compared to benign lesions. In that study, Muller et al suggested a threshold value of PUV max >1.9 and found that among 151 pathologically proven lesions, PEM had 100% sensitivity (26/26 lesions) and 96% specificity (120/125 lesions).…”
Section: Imaging Techniques and Interpretationmentioning
confidence: 99%